2013
DOI: 10.2340/16501977-1071
|View full text |Cite
|
Sign up to set email alerts
|

The reporting of blinding in physical medicine and rehabilitation randomized controlled trials: A systematic review

Abstract: Although the reporting of blinding in Physical Medicine and Rehabilitation randomized controlled trials shows some improvement over the past decade, it still does not fulfill current recommendations. Given its critical role in determining internal validity, stricter enforcement of CONSORT guidelines is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 43 publications
1
22
0
4
Order By: Relevance
“…Studies have shown that inadequate or unclear reporting in RCTs of concealed allocation [22][23][24][25] and blinding procedures is a common occurrence across a wide range of disciplines [26,27]; this is in line with the findings of the current review. These issues may be attributable to a lack of proper reporting rather than poor methodology.…”
Section: Discussionsupporting
confidence: 88%
“…Studies have shown that inadequate or unclear reporting in RCTs of concealed allocation [22][23][24][25] and blinding procedures is a common occurrence across a wide range of disciplines [26,27]; this is in line with the findings of the current review. These issues may be attributable to a lack of proper reporting rather than poor methodology.…”
Section: Discussionsupporting
confidence: 88%
“…It was found that although the reporting of blinding is deficient in PM&R, there is a trend for better reporting when comparing articles published in 2010 vs. 2000 (Villarmar et al . ). While blinding is an important issue to assess quality of clinical trials, one main challenge is that even studies that are double‐blinded and have appropriate reporting of blinding may still have unsuccessful blinding procedures.…”
Section: Discussionmentioning
confidence: 97%
“…Although patients were controlled in a within subject design, a natural recovery tendency or other confounding may have influenced results (Graham et al, 2012). In this design patients may also have reported improvement partly due to a placebo or Hawthorne effect (Villamar et al, 2013). Especially because patients have been treated in the national reference center for NA, which may have enhanced patient confidence in the treatment program.…”
Section: Study Limitationsmentioning
confidence: 99%